Accounting and Ms Excel: Which Features for Accounting Students? - Gitahi J. (European Scientific Journal, ESJ, 2022)
Rapid development in information technology (IT) has brought about significant changes in every field. In the accounting field, computer technology has become a major aspect of effective and efficient accounting. Today’s professional accountants need to have IT knowledge and skills that are relevant to their roles so as to provide competent and professional services. For new graduates entering the accounting profession, the ability to use various software and tools has increasing become very vital. This study assesses features of Ms Excel (Excel) that are used by professional accountants and the features of Excel that accounting graduates entering profession should be able to use.